Gender and the Lateral Angle of the Internal Acoustic Canal as Measured on MRI and Multislice CT - Büyükdemirci, Figen; Akansel, Gür; Gümüştaş, Sevtap; Akhun, Nilay; Kurtaş, Ömer; Bulut, Sanem Dereli (The Bulletin of Legal Medicine, 2010)
In this paper, to evaluate; the efficiency of multislice CT and MRI in determinination of gender by measuring the lateral angle of the internal acoustic canal meatus, if there is a difference between right and left lateral angle, and the correlation between age and the lateral angle. Lateral angles of both the righ and left internal acoustic canal meati were measured in 301 patients (163 females and 138 males) on axial slices of multislice CT scans of the temporal bone or on axial slices of MRI scans of the internal acoustic canal. The measurement technique was modified from a prior CT study by Akansel et al. Patiens were divided into three main groups as: all patiens (CT+MRI), CT only, MRI only. All main goups were divided into four subgroups according to age as follows: 0-9 years, 10-17 years, 0-17 years and older than 17 years. For measuring the lateral angle, bone algoritm was used for CT and the DRIVE sequence was used for MRI. The mean values from patients were compared statistically. There was no significant difference between the right and left side measurements with the exception of female CT patients of 0-9 years age. For all main groups and sub-goups, the mean lateral angle of the right and left internal acoustic canal was greater in females than in males and especially on adult grup (18 and older) this difference was statistically significant .The mean lateral angle measurements of the internal acoustic canal meatus on multislice CT and MRI are not different statistically between sides for both genders. Multislice CT and MRI can also be used as a way in determinination of gender by measuring the lateral angle of the internal acoustic canal meatus.Key words: Temporal bone, sex determination, multislice computerized tomograpy, magnetic resonance imaging
Keywords: temporal bone; sex determination; multislice computerized tomography; magnetic resonance imaging